2020
DOI: 10.1371/journal.pone.0236747
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum uric acid in ischemic stroke: A case-control study in Bangladesh

Abstract: Introduction Increased level of serum uric acid (SUA) is often considered a risk factor for ischemic stroke. This study was conducted to examine the association of SUA level with ischemic stroke and assessed gender-based differences, if any. Methods In this case-control study, neuroimaging-confirmed ischemic stroke patients were recruited as cases within three days of an incident from neurology in-patient department, and as controls, patients without stroke history were recruited from neurology outpatient depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Researches demonstrated that UA is an antioxidant factor to protect nerves from oxidative damage (6,7), thereby possibly preventing stroke outcomes. Whereas, many studies found that high SUA levels might be a major risk factor for the onset of stroke (8)(9)(10)(11). Zhong et al explored the association between SUA levels and risk of stroke base on a meta-analysis (12).…”
Section: Introductionmentioning
confidence: 99%
“…Researches demonstrated that UA is an antioxidant factor to protect nerves from oxidative damage (6,7), thereby possibly preventing stroke outcomes. Whereas, many studies found that high SUA levels might be a major risk factor for the onset of stroke (8)(9)(10)(11). Zhong et al explored the association between SUA levels and risk of stroke base on a meta-analysis (12).…”
Section: Introductionmentioning
confidence: 99%
“…Most epidemiological studies but not all of them suggested the existence of an association between elevated SUA levels and cardiovascular diseases (CVDs), such as stroke ( Lehto et al, 1998 ; Chien et al, 2005 ; Bos et al, 2006 ; Gerber et al, 2006 ; Hozawa et al, 2006 ; Kim et al, 2009 ; Chao et al, 2014 ; Li et al, 2014 ; Shi et al, 2017 ; Tu et al, 2019 ; Li J. et al, 2020 ; Zhang et al, 2020 ), CHD, arterial hypertension, and an increased risk for mortality due to CVDs in general population and subjects with confirmed CHD ( Ndrepepa, 2018b ; Khalil et al, 2020 ; Tatsumi et al, 2020 ). In the Saku study, HUA was found to be independently associated with the development of hypertension independent of alcohol drinking status ( Ndrepepa, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies have been included in this review. The following inclusion criteria were used based on the authors' discretion: patients with confirmed ischemic stroke, patients with confirmed hyperuricemia, and sample size >50 [9,17,36,[55][56][57][58][59][60][61].…”
Section: Literature Researchmentioning
confidence: 99%